DEVELOPMENT OF SCRACTH-BASED GAME MEDIA FOR LEARNING SCIENCE MATERIALS OF CHANGING THE FORM OF SUBSTANCE IN ELEMENTARY SCHOOL - Muhammad Taufik Dwi Putra; Lia Nurbanillah Fujianti; Tita Mulyati; E. Silmi Kaaffah; Mar’ati Fajrin (Universitas Pendidikan Indonesia, 2023)
Natural Science is a science that requires a scientific attitude, understanding of concepts and experimental skills. However, in its implementation in the field of education, there are still a lot of scores that do not reach the minimum criteria due to a lack of understanding of students' concepts and approaches that are still traditional. Therefore, in accordance with the capabilities of the 21st century, this study purposes to develop a game based media from Scratch that can be used by teachers and students in science learning material changes in the shape of objects. This research uses a method by applying Research and Development whose main purpose is to develop new products or improve existing products. The results of this study shows that the development of media based on the Scratch game can be developed by a teacher and can be used in learning with students. The results of testing the learning media that have been made on the display design aspect show a percentage of 93% which means it is very proper, the substance aspect of the material shows a percentage of 89% which means it is proper, and the respondent's response to the program shows a percentage of 83% which means it is proper.